2017
DOI: 10.1016/j.neuron.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Neurocentric View of Learning

Abstract: Synaptic plasticity (e.g. long-term potentiation; LTP) is considered as the cellular correlate of learning. Recent optogenetic studies on memory engram formation assign a critical role in learning to suprathreshold activation of neurons and their integration into active engrams (‘engram cells’). Here we review evidence that ensemble integration may result from LTP, but also from cell-autonomous changes in membrane excitability. We propose that synaptic plasticity determines synaptic connectivity maps, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
182
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(196 citation statements)
references
References 111 publications
14
182
0
Order By: Relevance
“…Intrinsic excitability changes may aid in driving memory formation, with synaptic plasticity serving to determine the information content by individual neurons (Titley et al . ). In cerebellar learning, this equates to a scaling of synaptic input weights depending on whether PF synapses contribute to the occurrence of an error.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Intrinsic excitability changes may aid in driving memory formation, with synaptic plasticity serving to determine the information content by individual neurons (Titley et al . ). In cerebellar learning, this equates to a scaling of synaptic input weights depending on whether PF synapses contribute to the occurrence of an error.…”
Section: Discussionmentioning
confidence: 97%
“…The details of mismatch at longer intervals could be explained by the involvement of multiple plasticity mechanisms in learning, some of which are triggered at longer time intervals. Indeed, it has been suggested that cerebellar motor learning rests on multiple mechanisms at multiple brain sites (Hansel et al 2001;Freeman & Steinmetz, 2011;Gao et al 2012;Titley et al 2017;Titley et al 2018).…”
Section: Timing Requirements Of Ltd and Learningmentioning
confidence: 99%
“…62,63 ) or on learning-related transcriptional changes other than those mediated by CREB 64,65 (for the potential utility of hypothesized long-term changes in excitability, see ref. 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy and invigorating debates related to the philosophical and the scientific basis of such analyses, with themes ranging from broad discussions on reductionism versus holism (Bennett & Hacker, ; Bickle, ; Jazayeri & Afraz, ; Krakauer, Ghazanfar, Gomez‐Marin, MacIver, & Poeppel, ; Panzeri, Harvey, Piasini, Latham, & Fellin, ) to more focused debates on the specific cellular components that are involved in specific aspects of coding and behavior (Bliss & Collingridge, ; Gallistel, ; Kandel et al, ; Kim & Linden, ; Martin et al, ; Mayford et al, ; Mozzachiodi & Byrne, ; Neves, Cooke, & Bliss, ; Otchy et al, ; Titley, Brunel, & Hansel, ; Zhang & Linden, ), have contributed to our emerging understanding of neural systems and their links to behavior. Several studies have covered the breadth and depth of these debates (Bargmann & Marder, ; Bennett & Hacker, ; Bickle, ; Jazayeri & Afraz, ; Jonas & Kording, ; Kandel et al, ; Katz, ; Kim & Linden, ; Krakauer et al, ; Lazebnik, ; Marder, ; Marder, ; Marder, ; Marder, O'Leary, & Shruti, ; Marder & Thirumalai, ; Mayford et al, ; Panzeri et al, ; Tytell, Holmes, & Cohen, ), and will not be the focus of this review.…”
Section: Degeneracy: Foundations From the Perspective Of An Encodingmentioning
confidence: 99%
“…In other words, the ability to undergo plasticity is an important requirement for it to encode or learn newly available information from the environment. Such plasticity has been shown to be ubiquitous, spanning cellular and network structures across almost all regions, and could be triggered by development (Desai, Cudmore, Nelson, & Turrigiano, ; Desai, Rutherford, & Turrigiano, ; Luo & Flanagan, ; Schreiner & Winer, ; Turrigiano & Nelson, ; White & Fitzpatrick, ), by learning processes (Kandel, ; Kandel et al, ; Kim & Linden, ; Lamprecht & LeDoux, ; Narayanan & Johnston, ; Titley et al, ; Zhang & Linden, ) or by pathological insults (Beck & Yaari, ; Bernard, Shah, & Johnston, ; Brager & Johnston, ; Grant, ; Johnston, Frick, & Poolos, ; Kullmann, ; Lee & Jan, ; Lehmann‐Horn & Jurkat‐Rott, ; Lerche et al, ; Poolos & Johnston, ). A traditional method to study such plasticity mechanisms is to subject neuronal or synaptic structures to specific activity patterns towards understanding the rules for plasticity in specific components.…”
Section: Degeneracy: Foundations From the Perspective Of An Encodingmentioning
confidence: 99%